2015
DOI: 10.1080/15384101.2015.1044174
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear PTEN tumor-suppressor functions through maintaining heterochromatin structure

Abstract: The tumor suppressor, PTEN, is one of the most commonly mutated genes in cancer. Recently, PTEN has been shown to localize in the nucleus and is required to maintain genomic stability. Here, we show that nuclear PTEN, independent of its phosphatase activity, is essential for maintaining heterochromatin structure. Depletion of PTEN leads to loss of heterochromatic foci, decreased chromatin compaction, overexpression of heterochromatic genes, and reduced protein stability of heterochromatin protein 1 a. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…It is increasingly evident that PTEN controls global chromatin architecture. For example, the heterochromatin structure is markedly impaired following PTEN deletion (Chen et al, 2014; Gong et al, 2015). Mechanistic studies revealed that PTEN physically interacts with a major heterochromatin protein, HP1α, and the linker histone H1.…”
Section: Pten As a Tumor Suppressormentioning
confidence: 99%
“…It is increasingly evident that PTEN controls global chromatin architecture. For example, the heterochromatin structure is markedly impaired following PTEN deletion (Chen et al, 2014; Gong et al, 2015). Mechanistic studies revealed that PTEN physically interacts with a major heterochromatin protein, HP1α, and the linker histone H1.…”
Section: Pten As a Tumor Suppressormentioning
confidence: 99%
“…[1][2][3][4] PTEN targets phosphatidylinositol-3,4,5-triphosphate (PIP3) and antagonizes the major survival pathway regulated by phosphatidylinositol 3-kinase (PI3K)/Akt. [5][6][7] Increasing evidence indicates that nuclear PTEN has fundamental functions in maintenance of chromosomal stability, 2,[8][9][10][11][12][13][14] suggesting there are as yet unidentified mechanisms in the process of chromosome inheritance for which the function of PTEN is indispensable. It has been shown that PTEN plays an essential role in maintaining the structural integrity of individual chromosomes, 2 which supports recognition of PTEN as a guardian of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have found that PTEN, which sustains chromosome condensation and heterochromatin structure [152,153], mediates fork progression and recovery during replication via recruitment of replication factor 1, Rad51 recombinase, and MCM2 helicase [167169]. These studies highlight the essential role of PTEN in maintaining chromatin condensation and ensuring efficient recruitment of vital replication factors for genome duplication.…”
Section: Chromatin Deregulation Genomic Instability and Cancermentioning
confidence: 85%
“…Recent research has uncovered new chromatin players and novel mechanisms of chromatin regulation, which helps understand the genome-epigenome interplay. For example, the tumor suppressor PTEN has been found to promote chromatin condensation by interacting with histones and other chromatin architecture proteins [152,153]. PTEN is among the most frequently mutated genes in human cancer.…”
Section: Chromatin Deregulation Genomic Instability and Cancermentioning
confidence: 99%
See 1 more Smart Citation